2023
DOI: 10.3390/jcm12062118
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Respiratory Microbiome in Hospitalized Patients with Asthma–COPD Overlap during and after an Exacerbation

Abstract: The immediate aim of this study was to comparatively examine the bacterial respiratory microbiome of patients in a stable state and during an exacerbation of asthma–COPD (chronic obstructive pulmonary disease) overlap (ACO). This prospective observational study took place in Jordan between 1 September 2021 and 30 April 2022. Sputum samples from patients with recognized ACO were acquired within 48 h of the exacerbation onset and again at 3 weeks following the exacerbation. The next-generation sequencing Illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
(71 reference statements)
0
15
0
2
Order By: Relevance
“…Moreover, high-throughput Illumina MiSeq, used in this recent work [34], revealed a large amount of bacterial variety in sputum. Similar to earlier COPD investigations utilizing culture techniques, this study found substantial abundances of the bacterial aerobic genera Streptococcus, Haemophilus, Pseudomonas, and Moraxella [35,36].…”
Section: Respiratory Microbiome and Aco During Stable And Exacerbatio...mentioning
confidence: 82%
See 3 more Smart Citations
“…Moreover, high-throughput Illumina MiSeq, used in this recent work [34], revealed a large amount of bacterial variety in sputum. Similar to earlier COPD investigations utilizing culture techniques, this study found substantial abundances of the bacterial aerobic genera Streptococcus, Haemophilus, Pseudomonas, and Moraxella [35,36].…”
Section: Respiratory Microbiome and Aco During Stable And Exacerbatio...mentioning
confidence: 82%
“…In this study, the lower airways of clinically stable ACO patients were found to have bacterial colonization, which makes it challenging to establish the role of bacteria in exacerbation. The examination also revealed significant differences between the study groups [34].…”
Section: Respiratory Microbiome and Aco During Stable And Exacerbatio...mentioning
confidence: 88%
See 2 more Smart Citations
“…Известно, что распространение нового коронавируса SARS-CoV-2 сопровождалось существенным ограничением циркуляции целого ряда возбудителей сезонных респираторных инфекций, за исключением риновирусов и респираторно-синцитиального вируса [5]. Согласно полученным нами данным, в этот период самыми распространенными оказались риновирусы вида A, что соотносится с другими исследованиями [2,21,40]. Также нами установлены возрастные и клинические различия в зависимости от вида риновирусов.…”
Section: результатыunclassified